2015
DOI: 10.3126/kumj.v12i3.13715
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Hospital Vs Home Self Administration of Vaginal Misoprostol for Medical Abortion

Abstract: BackgroundA combination of mifepristone followed after 24 hrs by misoprostol has proved a safe and effective abortifacient for termination of early pregnancy. Home use of misoprostol for medical abortion is still controversial in many countries including ours where women's literacy rate is low. Particularly in developing countries, this method markedly decreased the hospital visit which would be beneficial to patients and hospital staff. ObjectiveTo see whether the home self administration of vaginal misoprost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…29 In a prospective, comparative, non-randomized, open-label study in Nepal, Conkling et al found that self-administration of vaginal misoprostol was safe and effective for termination within 63-day LMP. 30,31 In this study, we found that home administration of low-dose misoprostol was highly acceptable. Although the satisfaction rates for the H-Mis and S-Mis groups were both high, participants indicated that they preferred self-administration owing to convenience and privacy protection.…”
Section: Self-administration Advantagesmentioning
confidence: 69%
See 1 more Smart Citation
“…29 In a prospective, comparative, non-randomized, open-label study in Nepal, Conkling et al found that self-administration of vaginal misoprostol was safe and effective for termination within 63-day LMP. 30,31 In this study, we found that home administration of low-dose misoprostol was highly acceptable. Although the satisfaction rates for the H-Mis and S-Mis groups were both high, participants indicated that they preferred self-administration owing to convenience and privacy protection.…”
Section: Self-administration Advantagesmentioning
confidence: 69%
“…In a prospective, comparative, non‐randomized, open‐label study in Nepal, Conkling et al . found that self‐administration of vaginal misoprostol was safe and effective for termination within 63‐day LMP …”
Section: Discussionmentioning
confidence: 98%
“…Three studies were RCTs, and included data from 1452 women. [21][22][23] Sixteen studies were NRSs and included data from 10 124 women. 16 17 24-36 Sixteen studies were conducted in lowto-middle resource settings (Bangladesh, 25 26 India, 28 30 34 Nepal, 22 31 China, 21 23 Vietnam, 32 33 35 Tunisia, 29 35 Nigeria, 36 Albania 27 and Turkey 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…35 Participants' maximum gestational age was under 9 weeks for 14 studies, 16 17 21 23 24 27- 29 31-35 and up to and including 9 weeks for the other five studies. 22 25 26 30 36 Statistically significant differences between participants in the homebased and clinic-based groups were reported on variables including primigravida, parity, age and gestational age in six studies. 16 17 28-30 32 All studies used a combination regimen that involved the administration of mifepristone and misoprostol.…”
Section: Resultsmentioning
confidence: 99%
“…5 Several studies have studied the vaginal use of misoprostol. 1,5,8 Our study evaluated the efficacy, side effects and acceptability of its sublingual use.…”
Section: Discussionmentioning
confidence: 99%